It`s a muSt win: the effects of self-talk to enhance passing performance under pressure in elite football players - Viscosi, J.; Robazza, C.; Jansson, B.; Davis, P.; Ruiz, M. C. (The Sport Psychologist, 2024)
Strategic self-talk is a powerful mental skill that athletes can use to self-regulate the effects of pressure and enhance task performance. Multistates (MuSt) theory considers the combination of emotion- and action-centered self-regulation to be the most effective strategy to optimize athletes` performance and subjective experience. The aim of this study was to test the tenets of MuSt theory on a pressurized performance task, involving male junior football players (N = 20, Mage = 18.6) competing at the elite level in Finland. The task tested the players` passing abilities over six trials while they applied different self-talk strategies in attempts to improve passing performance. The findings demonstrate the effectiveness of strategic self-talk as a form of self-regulation. Specifically, the combination of emotion- and action-centered cue words proved to be the optimal strategy for coping with the demands of the task. The study findings have relevant practical implications for players, coaches, and practitioners.